Analysis of the Synergy of the Penta Helix Model in Handling COVID-19 at the Pekanbaru City Level - Ardiansyah Ardiansyah; Suparto Suparto; Wira Atma Hajri; M. Rafi; Pahmi Amri (Journal of Contemporary Governance and Public Policy, 2023)
The government has a crucial role in the management of COVID-19 since it is a leader. However, to speed up breaking the chain of transmission of COVID-19, the government needs various solutions from various stakeholders, considering that the COVID-19 pandemic is a broad problem and all parties are required to work together to achieve this goal. This study aims to explain the influencing factors and implications of the Penta Helix synergy in handling COVID-19 at the Pekanbaru City Level. This study then used a qualitative analysis method with Nvivo 12 Plus as an analytical tool to help visualise data from online media. The findings of this study indicate that the factors that influence the synergy of the Penta Helix model in handling COVID-19 at the Pekanbaru City Level include the role of government, involvement, and equality between actors, joint decision-making processes, formal organization, consensus, and collaboration factors in problem-solving. Then, the synergy of the Penta Helix model in handling COVID-19 in Pekanbaru City has two impacts, namely, the implications for developing the spirit of cooperation and accelerating the handling of the COVID-19 pandemic in Pekanbaru City. The implications of this research provide a reference for the importance of strengthening actor synergy based on a systematic mapping of the balance of roles of each stakeholder to optimally contribute to handling COVID-19 at the Pekanbaru City Level.